Pengaruh Job Insecurity, Budaya Organisasi, dan Kepuasan Kerja Terhadap Komitmen Organisasional Karyawan Pabrik Gondorukem dan Terpentin (PGT) Sukun, Kecamatan Pulung, Kabupaten Ponorogo - Silfi Qowiyu Dianingtias; Sri Hartono; Dwi Warni Wahyuningsih (Journal on Education, 2024)
This research aims to determine the effect of Job Insecurity, Organizational Culture, and Job Satisfaction on Organizational Commitment of Employees of Gondorukem and Turpentine Factory (PGT) Sukun, Pulung District, Ponorogo Regency. The research method used is quantitative research. The sample in this study used a nonprobability sampling method, namely by using the entire population of 55 employees. The data collection technique in this study was to distribute questionnaires to PGT Sukun employees. The data in this study were processed using the SPSS version 26 application which obtained the results that partially job insecurity has no effect on organizational commitment, organizational culture has a positive and significant effect on organizational commitment, job satisfaction has a positive and significant effect on organizational commitment. Simultaneously job insecurity, organizational culture, and job satisfaction have a positive and significant effect on organizational commitment of employees of the Gondorukem and Turpentine Factory (PGT),Sukun Pulung District, Ponorogo Regency.